Sosialisasi Literasi dan Inklusi Keuangan Pada SMK Bougenvile Lubuk Basung - Nofritar Nofritar; Yuliarman Mahmudin; Andre Ilyas; Dewi Sartika; Nini Nini; Yentisna Yentisna (LPPM Universitas Dharma Andalas, 2023)
This time the community service is aimed at Bougenvile Vocational School students located on Jl. Patih Aminuddin No. 177 Parit Rantang Mudik nagari Lubuk Basung, Lubuk Basung District. This community service aims to provide education to Bougenvile Vocational High School students about financial literacy and financial inclusion. The method for implementing Community Service activities consists of three stages of activity. The first stage of preparation includes pre-survey, team formation, preparation and submission of proposals, team and partner coordination and preparation of training tools and materials. The second stage is the screening stage, in the form of preparing speakers, ensuring complete supporting facilities and infrastructure, consumption, surprises and others. The third stage is the activity implementation stage. Provide material on motivation, financial literacy and financial inclusion. Evaluation is carried out by comparing the conditions of the partners before and after the implementation of the program using interview and observation methods. By carrying out this activity, SMK Plus Banking students have a deep understanding of financial literacy and inclusion. After that, a report is prepared for further publication in the form of articles in electronic media/national journals.